The Emissions Gap Report 2013 - United Nations Environment Programme (United Nations Environment Programme, 2013)
The report presents the latest estimates of the emissions gap in 2020 and provides plentiful information about: - current (2010) and projected (2020) levels of global greenhouse gas emissions, both in the absence of additional policies and consistent with national pledge implementation - the implications of starting decided emission reductions now or in the coming decades - agricultural development policies that can help increase yields, reduce fertilizer usage and bring about other benefits, while reducing emissions of greenhouse gases - international cooperative initiatives that, while potentially overlapping with pledges, can complement them and help bridge the emissions gap